2013
DOI: 10.18869/acadpub.johe.2.4.183
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ultraviolet radiation exposure of welders working in Shahrud City, Iran, 2014

Abstract: Background: Farmers and welders who work in open spaces and are exposed to direct sunlight are often exposed to sunlight radiation types of skin cancer. The aim of the present welders working in Shahrud City Materials and Methods: This cross a.m. to 3 p.m. in indoor environments ultraviolet radiation (UVR) meter was used utilized using factory instruction and self-reporting, and information related to UV analyzed. Results:The results showed that average UVR exposure with personal protection was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The younger age group involvement suggests the early age apprenticeship through hands on training from experienced welders at the start of the job. It was found that about 85.3 % respondents were married, a finding similar in India [18]. …”
Section: Discussionmentioning
confidence: 73%
“…The younger age group involvement suggests the early age apprenticeship through hands on training from experienced welders at the start of the job. It was found that about 85.3 % respondents were married, a finding similar in India [18]. …”
Section: Discussionmentioning
confidence: 73%